2011
DOI: 10.5304/jafscd.2011.014.016
|View full text |Cite
|
Sign up to set email alerts
|

Informal and Formal Mechanisms of Coordination in Hybrid Food Value Chains

Abstract: The challenges of meeting growing consumer demand for local food, especially from larger, institutional buyers, has sparked many to look beyond direct marketing to alternative models of produce aggregation and distribution. Value chains that incorporate conventional food system infrastructure are one such model for local food system development, but little research has studied their functioning and outcomes. Arrangements where conventional produce distributors handle local food can be viewed as "hybrid" food v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2103
2103

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…In prior research on cross-scale food supply chains, researchers and practitioners have suggested that collaborative relationships require trust (Abatekassa & Peterson, 2011;Bloom & Hinrichs, 2011;Clark & Inwood, 2015). As we have seen in this case, growers and buyers had interpersonal trust, believing in the inherent integrity of partners, but low confidence in the reliability of their trading partners, due to factors perceived as beyond their trading partners' control.…”
Section: Recommendations For Practitionersmentioning
confidence: 75%
See 1 more Smart Citation
“…In prior research on cross-scale food supply chains, researchers and practitioners have suggested that collaborative relationships require trust (Abatekassa & Peterson, 2011;Bloom & Hinrichs, 2011;Clark & Inwood, 2015). As we have seen in this case, growers and buyers had interpersonal trust, believing in the inherent integrity of partners, but low confidence in the reliability of their trading partners, due to factors perceived as beyond their trading partners' control.…”
Section: Recommendations For Practitionersmentioning
confidence: 75%
“…Local food sold through intermediated market channels is often described in terms of SFME's "scaling-up" for larger markets (e.g., Day-Farnsworth, McCowan, Miller, & Pfeiffer, 2009;Friedmann, 2007;Heiss, Sevoian, Conner, & Berlin, 2015). One strategy to build cross-scale connections between SMFEs and larger buyers is for product to "piggy-back" on conventional distributional and retail infrastructure (Bloom & Hinrichs, 2011;Clark & Inwood, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, deliberate values-based engagement and commitment to noneconomic goals can lead to successful interorganizational coordination in hybrid food value chains that build aggregation and distribution in local food systems on pre-existing conventional infrastructure (Bloom & Hinrichs, 2011). Investigation of U.S. counties on the rural/urban interface have shown the importance of government programs and supportive governance frameworks.…”
Section: Social and Institutional Dynamics Influencing Production In mentioning
confidence: 99%
“…As emphasized in the literature, in fact, VBSCs are often created through hybrid (Bloom & Hinrichs, 2011) enterprise coalitions. Our AOTM case study review reveals that values-based agrifood businesses often partner strategically with enterprises that are part of the conventional agrifood system in order to process, distribute, and sell their product.…”
mentioning
confidence: 99%